Dryobalanoxylon sp. : Silicified Fossil Wood from Lebak Regency, Banten Province, Indonesia - Hanny Oktariani; Winantris winantris; Amir Hamzah (Jurnal Geologi dan Sumberdaya Mineral, 2019)
Abstract- Two fossil wood were discovered from Sindangsari Village, Sajira District, Lebak Regency, Banten Province, Indonesia. They were preserved within tuffaceous rocks of the Genteng Formation in Early Pliocene age in littoral to terrestrial environment deposition. To identify mineral composition of the silicified wood, XRD analyser method was applied. Result of XRD analyses shows that both of fossil wood are Dryobalanoxylon sp. consist of quartz mineral with d value is 3.358 Å and 3.350 Å Keywords : Dryobalanoxylon, Early Pliocene, Genteng Formation, Quartz